2020
DOI: 10.3390/antibiotics9100695
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Biological Evaluation of New Pyridothienopyrimidine Derivatives as Antibacterial Agents and Escherichia coli Topoisomerase II Inhibitors

Abstract: The growing resistance of bacteria to many antibiotics that have been in use for several decades has generated the need to discover new antibacterial agents with structural features qualifying them to overcome the resistance mechanisms. Thus, novel pyridothienopyrimidine derivatives (2a,b–a,b) were synthesized by a series of various reactions, starting with 3-aminothieno[2,3-b]pyridine-2-carboxamides (1a,b). Condensation of compounds 1a,b with cyclohexanone gave 1’H-spiro[cyclohexane-1,2’-pyrido[3’,2’:4,5]thie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 51 publications
0
10
0
Order By: Relevance
“…Moreover, two-fold serial dilution approach was used to find out the Minimum Inhibitory Concentration (MIC) values (expressed in μg mL −1 ) for the examined compounds. 68,69 The obtained data were recorded in ( Table 4 ).…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, two-fold serial dilution approach was used to find out the Minimum Inhibitory Concentration (MIC) values (expressed in μg mL −1 ) for the examined compounds. 68,69 The obtained data were recorded in ( Table 4 ).…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, we need to choose three of the most important antimicrobial target enzymes to study the ability of our compounds to inhibit them using molecular docking technique; the best methods to expect the inhibitory activity theoretically. In addition, the presence of the pyridine ring encourages us to study the tree enzymes, since pyridine has a broad spectrum of biological activity and is a good inhibitor for Gyrase B and topoisomerase [ 34 ].…”
Section: Resultsmentioning
confidence: 99%
“…El-Deen et al [ 82 ] reported the synthesis of the pyridothienopyrimidine derivatives 196 – 198 in good yields (70–81%) from compounds 195a – 195b , as can be seen in Scheme 42 . The in vitro evaluation of these compounds against six strains of both Gram-positive ( S. aureus , B. Subtilis , B. cereus ) and Gram-negative ( E. coli , S. typhimurium , P. aeruginosa ) bacteria compared with Amoxicillin trihydrate as a reference drug showed a significant antibacterial activity for all compounds, especially against Gram-negative strains, with MIC values ranging from 7.81 to 62.5 μg mL −1…”
Section: Synthesis Of Fused Pyridines With Other Heterocycles With An...mentioning
confidence: 99%